Monitoreo y mapificación del estado actual de los suelos por su reacción mediante el uso de los sig del cantón Chilla provincia de El Oro - Jaya Sedamanos, Ana Julia (2007)
The soil is an attaché of not consolidated minerals and of organic particles taken place by the combined action of the wind, the water and the processes of organic disintegration, and for the knowledge of the conditions and knowledge which it is its topography, the Systems of Geographical Information are using at the present time (SIG). The SIG, are tools each time more used in the planning. The formation of a geographical database of the production areas is one of the stages of the classification and of the planning of the agriculture. By means of the tools of the SIG we will obtain a knowledge of the hardware, software and designed data, which will allow to obtain the cartographic letters in digital form of different places of the canton Chilla, with the technical advice of the Integrated Center of Environmental Geomática (CINFA), of the National University of Loja, he/she was carried out the Monitoreo and Mapificación of the current state of the soils for their reaction, by means the use of GIS, of the Canton Chilla, El Oro Province. The Objectives were the following ones: 1. To characterize the floors of the Canton Chilla, for their acidity, and alkalinity, 2.To determine, the pH, the Capacity of Exchange Catiónico (CIC), the Electric Conductivity (you leave), and the percentage of interchangeable Sodium, to classify them as saline, saline - sodium, sodium and normal, 3. To recommend, the technically appropriate quantity of amendment, for their recovery and later handling, 4. To elaborate the maps of current use, slopes, salinity, acidity, and pattern of cultivations, with the use of the Systems of Geographical Information (SIG), of the Canton Chilla El Oro province, 5. To diffuse the results to the development Institutions, so much public as private, and people linked with the agricultural sector. The used methodology was in the field the taking of samples directly georeferenciadas with a GPS navigator, in grill form each two Km. to 20 cm of depth, to complete the first objective the protocol of the potenciómetro, for the second objective the protocol of Chapman (CIC), Conductómetro, and that of the espectrofotómetro of atomic absorption, for the third objective was carried out the recommendations of having whitewashed, to complete the fourth objective it was used the systems of geographical information as Easy it traces, letter linxk, and arc view 3.2, to carry out the maps of slopes, chromatic classes, of textures, current use of the soil, pattern of cultivations, ph of soils, sampling, map bases.